Intra-Household Inequality in Food Consumption and Diets in the Philippines - Dizon, Felipe (World Bank, Washington, DC, 2022)
Most welfare measures, including food expenditure and diet quality, are based on household aggregates and assume an equal or equitable distribution of resources among members within the household. But it is unlikely that resources are distributed equally or equitably within most households. As such, individual food expenditure and diet quality measures, rather than household aggregations, may paint a more accurate picture of intra-household welfare. This paper assesses the disparity between household and individual measurement of food expenditure and diet quality in the Philippines using data from 2013. It finds evidence of intra-household inequality for food expenditure and for diet quality. In particular, for the consumption of starchy staples, meat, fish, and legumes, women and children do not meet the recommended consumption, even within households that, in aggregate, are able to meet the recommended consumption. However, intra-household inequality is not observed under circumstances in which no one in the household meets recommended consumption, as is the case for many food categories in our analysis.